Studi Pengaruh Variasi Partikel Shotpeening terhadap Struktur Mikro dan Sifat Mekanis pada Aluminium Paduan - Wartono; Rivan Muhfidin; Eka Yawara; Sumpena (Proklamasi 45 University, 2025)
The objective of this research is to find out the effect of shotpeening particle variations on the microstructure, tensile strength, and impact strength of friction stir welding (FSW) joints. In the weld metal area after the material is subjected to friction stir welding (FSW), the material will experience softening and a decrease in mechanical properties compared to the raw material. The shotpeening process on the weld metal surface is expected to improve mechanical properties, because the weld metal surface will experience repeated pressure from the shotpeening particles as a forging effect. Friction welding (FSW) is carried out on materials made of 6061 aluminum alloy and the material has a thickness of 3 mm, with butt joint welding. The friction welding process uses an Aciera brand milling machine, the feeding speed on the machine is set to 18 mm / minute and the spindle rotation is 910 rpm. Shotpeening particles use steel ball and aluminum oxide, namely S 230, Al 24, Al 54. The results of microstructure testing show that the forging effect of shotpeening causes deformation in the surface layer to a depth of 700 µm. The results of tensile testing on FSW joints with variations in shotpeening particles: S 230, Al 24, Al 54 show the optimum tensile strength in shotpeening with Al 54 particles of 208 MPa, and the results of impact testing show the optimum impact price in shot peening with S 230 particles of 0.57 J / mm2.